Jumping Motion Based on Momentum Optimization Control and Differential Dynamic Programming for a Multilocomotion Robot. Issue 5 (24th February 2022) - Liu, Guoshuai; Lu, Zhiguo; Wang, Ruchao; Zhao, Haibin; Liu, Chong; Shi, Xinhao
Abstract: Jumping motion is an indispensable motion mode for a multilocomotion robot, which will improve the crossing ability of the robot. This paper proposes a novel jumping control scheme for an MLR to perform jumping motion. The control strategy divides the whole jumping motion into three phases: the launch phase, the flight phase, and the landing phase. In the launch and landing phases, the controller is designed based on the centroid dynamics. By controlling the centroid momentum, the robot can achieve the desired centroid trajectory to obtain the initial take‐off speed in the launch phase and to maintain stability and reduce impact in the landing phase. In the flight phase, Differential Dynamic Programming algorithm is used to adjust the posture of the robot to further improve the jumping height and prepare for a smooth landing. Finally, the effectiveness of the proposed method is evaluated through simulations. Abstract : This paper proposes a novel jumping control scheme for a multilocomotion robot to perform jumping motion. It is designed based on the centroid dynamics and Differential Dynamic Programming algorithm. The controller enables the robot to obtain a take‐off speed in the vertical direction, to complete the posture adjustment in flight, and to reach a jumping height of 0.29 m.